Perspektif Kim Knott tentang Insider-Outsider dalam Studi Agama - Sujiat Zubaidi Saleh (Religió: Jurnal Studi Agama-agama, 2014)
Contemporary discourse of religious studies indicates many fields of study in understanding religion. Religious spectrum not only relates with credo, faith, worldview, theology and etcetera but expanding in various aspect (cultural and historical side). The cultural and historical aspects in a certain point give some problems in academic field. Kim Knott based on those matters tries to give a new shot in analyzing religion based on the issued aspects. Looking at how complicated is it Kim Knott maps it into two religious approaches. First is the hardship situation to make such a clear gap between religious and not-religious territory and second is the complicated problem in relation with religion as tradition and religion as faith. This article elucidates a viewpoint of Kim Knott as a “new outline” on religious studies. Knott attempts to eliminate the subjective intentions by using two basic perspectives of methodology: insider and outsider. He has classified the concept of inter-connection between social and religious role into four elements: pure participant, researcher as participant, participant as researcher and pure researcher. However, this concept remains an important problem concerning to standard of objectivity. Knott’s approach tries to place researcher on the margin of appreciation as a border line between insider-outsider.